ASSESSING THE FINANCIAL AND MANAGEMENT STRENGTH OF ISLAMIC REAL ESTATE INVESTMENT TRUSTS (I-REITs) DURING THE GLOBAL FINANCIAL CRISIS (GFC) - Atasya Osmadi; Muhammad Najib Razali (PERINTIS eJournal, 2021)
By the end of 2008, there were only three Islamic REITs in the world, with all three in Malaysia, namely Al-‘Aqar KPJ REIT (hospital properties), Al-Hadharah Boustead REIT (plantation properties) and Axis REIT (office/industrial properties). Axis REIT, which was the first Malaysian REIT, has reclassified itself as an Islamic REIT in December 2008. This paper will provide an increased understanding of the Islamic M-REITs performance in terms of its financial and management strength during the global financial crisis from 2007 to 2009. The result gave us an understanding on the relevance of the Islamic M-REIT development and the expected future growth in Islamic property investment products with opportunities globally. The findings have revealed the competitiveness of I-REITs in terms of financial and management strength within M-REITs although hit by GFC. This indicates that the Islamic principles outdid the more volatile conventional principles during the GFC.